Evaluation of urinary calcium to creatinine ratio as a predictor of preeclampsia - Solanki, Garima; Agrawal, Sunita; Dora, Arun K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertension in pregnancy is a big threat to the mother as well as the fetus. Prediction of preeclampsia with reasonable accuracy is one of the essential prerequisites for its prevention. Various biological markers are available for the prediction of preeclampsia but none of those is reasonably reliable, valid and economical. In this present study, the predictive value of the urinary calcium-creatinine ratio (CCR) for the prediction of preeclampsia was studied. Methods: This Prospective, observational study was conducted in the department of obstetrics and gynecology, Jawaharlal Nehru Hospital, Bhilai, Chhattisgarh, India. The study population was comprised of consecutive 174 pregnant women with gestational age between 20-28 weeks attending antenatal OPD. Calcium and creatinine levels were estimated in the midstream clean catch urine sample. After initial workup, all patients were followed in the antenatal clinic till the time of delivery. The number of patients who develop the hypertensive disorder in pregnancy was noted and the correlation studied. Results: On statistical analysis, CCR at ≤0.04 had a sensitivity of 71.43%, specificity of 98.75%, and the positive predictive value of 83.33% and negative predictive value of 97.53%. The accuracy of the test was 96.55%. Conclusions: A single estimation of calcium to creatinine ratio in asymptomatic pregnant women between 20-28 week of gestation is a simple and cost-effective test. A value of less than or equal to 0.04, in a spot urine sample, has a good predictive value for preeclampsia.